Effect of female size on fecundity and survivorship of Aedes aegypti fed only human blood versus human blood plus sugar - Amara T. Naksathit (2018)
We determined whether size, an indirect measure of teneral energy reserves, modifies the fitness advantage (∑ survival X egg production/female/day) conferred to female Aedes aegypti (L.) maintained on human blood over cohorts fed human blood plus sugar. Different sized females were obtained by rearing them at different larval densities and with different amounts of food per larva. Each female in 4 treatment groups of 23 mosquitoes each was maintained in a separate cage. A 10% sucrose solution was provided ad libitum to mosquitoes in the sugar-plus-blood treatments and water to the blood only groups. Eggs deposited and survival were monitored daily for each mosquito until all had died. Within a size category, survival of mosquitoes in different treatments was not different and mosquitoes fed only human blood laid more eggs than those fed blood plus sugar. The numbers of eggs laid by small mosquitoes fed human blood alone and large mosquitoes fed human blood plus sugar were not different. Mosquitoes fed only human blood had higher net replacement and intrinsic rates of growth than similar sized mosquitoes fed blood plus sugar. Female Ae. aegypti fed only human blood, regardless of the variation in size that we studied and thus energy reserves at emergence, had a fitness advantage over those fed a diet that included sugar.